Fibrin clot properties and haemostatic function in men and women with type 1 diabetes - Tehrani, Sara; Jörneskog, Gun; Ågren, Anna; Lins, Per-Eric; Wallén, Håkan; Antovic, Aleksandra (Thrombosis and Haemostasis, 2015)
The increased risk of vascular complications in type 1 diabetes may in part be explained by changes in haemostatic function. In the present study, we investigated the fibrin clot properties in patients with type 1 diabetes in relation to sex and microvascular complications. The study included 236 patients (107 women) aged between 20–70 years and without any history of cardiovascular disease. Fibrin clot properties, assessed by determination of the permeability coefficient (Ks) and turbidimetric clotting and lysis assays, did not differ between men and women. Compared with men, women had worse glycaemic control as well as higher levels of prothrombin fragment 1+2 and peak thrombin generation in vitro, indicating increased thrombin generation both in vivo and in vitro. Subgroup analyses of patients younger than 30 years revealed less permeable fibrin clots and prolonged lysis time in females compared with age-matched men. Patients with microvascular complications had higher fibrinogen concentrations and denser and less permeable fibrin clots. Thus, we conclude that in vitro fibrin clot properties in patients with type 1 diabetes without cardiovascular disease are not different between the sexes, but associate with prevalence of microvascular complications. Tighter fibrin clot formation in younger women, as suggested by our results, may affect their future cardiovascular risk and should be investigated in a larger population.
Keywords: Fibrin clot; type 1 diabetes; microangiopathy